Perlindungan Hukum Bagi Franchisee Dalam Hal Pemutusan Perjanjian Waralaba (Studi Kasus Salon De Grace dan Salon Yemember - Suhartiwy, Ovy; , Kelik Wardiono, S.H., M.H., cdDR (2016)
Business cooperation of mutual benefit in the franchise system is a necessity for both, franchisor and franchisee has similar interests to develop their business within a structure of integrated system and related to each other.The results of this research are expected to provide benefits to the business world in the development later in life and also for the community can be one of the input materials useful in entering the business world, especially in the field of franchising. This research was based on legal research conducted by doctrinal approach. Type of study in this study are more descriptive. Sources of data in this research is secondary data. Secondary data is data derived from the ingredient library. In this research, secondary data include Decision No. 31 / ARB / BANI-SBY / I / 2012. The data have been collected and processed will be discussed using qualitative. Based on normative research result shows that considerations Arbiter Assembly stating that the actions of the Defendant, in the form of (1) Defendant violated clause of Article 5 and Article 6 letter c Deed No. 34 (2) Defendant violated the provisions of Article 6 letter b Deed No. 34 (3) Defendant refuses to make a payment on the franchise shortage of Rp. 20,000,000.00 (Twenty Million). Legal considerations of the Council of Indonesian National Board of Arbitration Surabaya of Royalty fee of 3% (three percent) of the turnover Royalty clean. The verdict of the Indonesian National Board of Arbitration Surabaya in decision No.31/ARB/BANI-SBY/l /2012, where the verdict is: grant to partially over the petition filed; BANI states authorized to decide disputes; Franchise declared the Cooperation Agreement has expired; punish the Respondent to pay court costs and ordered the Secretary Assembly to officially register the judgment in the District Court of Surabaya.